Injury of the Lumbard in Degenerative Diseases of the Lumbar Spine - R. Israilov; B. Mamajonov (Zien Journals, 2023)
In this study, the pathomorphological changes that develop in the yellow ligament of the spinal canal in all types of degenerative diseases of the lumbar region of the spine were studied. As a material, fragments of corpus luteum covering the back border of the spinal canal were taken. The results show that in some degenerative diseases of the lumbar region, the yellow ligament is only hypertrophied, while in others, dystrophy, calcification develop, and ossification and deformation are observed in others. Hypertrophy and thickening of the yellow ligament of the spine develops after degenerative and inflammatory diseases and begins with the increase of histitic cells around the blood vessels and in the interstitial tissue. The hypertrophy of the yellow ligament is manifested by a sharp increase in collagen fibers, the development of the fibroelastosis process, the breakdown and destruction of elastic fibers, and a decrease in their quantity.
Keywords: spine; yellow ligament; degenerative diseases; morphology